Enhanced absorption and EQE of Si MSM photodiodes with integrated periodic arrays of holes. Issue 1 (September 2021) - Gou, Jun; Xie, Zheyuan; Yu, He; Liu, Xianchao; Wang, Jun
Abstract: In order to enhance the absorption of thin Si film, cylindrical-shaped holes arranged in square and hexagonal lattices with different designs of hole diameter, depth and period are integrated in the surface of Si films with a thickness of 1.5 μm and 2.5 μm on either bulk Si or SOI substrate. At the wavelengths between 800 950 nm, light bending and absorption enhancement of Si film with integrated hole array is analyzed by FDTD simulation. Hole array with a period similar to the wavelength and a diameter/period ratio around 0.7 enables a higher absorption of Si film. Si film with cylindrical-shaped holes in hexagonal lattice with a Si thickness of 1.5 μm and a hole depth of 250 nm provides an absorption of 43.16 % at 850 nm wavelength on a SiO2 substrate. Nanostructured Si MSM photodiodes are fabricated by integrating periodic arrays of holes in 1.5 μm thin absorption regions between metal fingers. The EQE is enhanced to 61 % at 850 nm, while the photodiodes without holes show only 23 %.